ANALISIS PENERAPAN HUKUM KELUARGA ISLAM DI ARAB SAUDI - Sunoto; Azmil Fauzi Fariska (JURNAL CERDAS HUKUM, 2022)
In all aspects of life, Saudi Arabia formulates its country's rules based on the Qur'an and hadith, including regarding family law. In its development, Islamic countries throughout the world are required to maintain the rules of Islamic law. But on the other hand, the era of globalization is forcing Islamic countries to reform some rules that intersect with family law in their respective countries. The desire of Muslims to maintain and apply Islamic law in their country is very logical. Because Muslims believe that their religious rules have comprehensive teaching values. This paper will look at how Saudi Arabia maintains Islamic family law in its country in the midst of the current swift currents of globalization. The results of this study show that Islamic family law in Saudi Arabia still maintains the Hambali school as the main school in referring to the rules of family law in Saudi Arabia. In its implementation, marriage law in Saudi Arabia still adheres to uncodified law. In general, countries that still apply uncodified law as the legal basis for marriage in Muslim countries, the contract refers to the madzahb books that they adhere to. And those who carry out these rules are in the hands of scholars or religious institutions that are authorized by the kingdom or state. In the context of Saudi Arabia, the institution that has the authority to carry out and supervise the application of the family law is the mufti institution.